S-Band Gain Improvement Using a Thulium–Aluminum Co-Doped Photonic Crystal Fiber Amplifier - Emami, S.D.; Muhammad, A.R.; Muhamad-Yasin, S.Z.; Mat-Sharif, K.A.; Zulkifli, M.I.; Adikan, Faisal Rafiq Mahamd; Ahmad, Harith; Abdul-Rashid, H.A. (Institute of Electrical and Electronics Engineers (IEEE), 2014)
An extended method for gain and noise figure enhancement in the S-band using a thulium-doped photonic crystal fiber amplifier (TD-PCFA) is proposed and shown by numerical simulation. The principle behind the enhancement is the suppression of unwanted amplified spontaneous emission (ASE) using the PCF structure. This proposed PCF achieves the intended band-pass by doping the cladding with high index material and realizes appropriate short and long cut-off wavelengths by enlarging the air-holes surrounding the doped core region. The PCF geometrical structure is optimized so that high losses occur below the short cut-off wavelength (800 nm) and beyond the long cut-off wavelength (1750 nm). Furthermore, the PCF geometrical structure design allows for high ASE suppression at 800- and 1800-nm band, thus increasing the population inversion needed for amplification in S-band region as the 1050-nm pump propagates light in the band-pass. The proposed TD-PCFA demonstrates gain enhancements of 3-6 dB between 1420 and 1470 nm.